Epithelioid inflammatory myofibroblastic sarcoma: a case report and brief literature review - Dou, Weidong; Guan, Yu; Liu, Tao; Zheng, Hang; Feng, Shuo; Wu, Yingchao; Wang, Xin; Liu, Zhanbing (Frontiers in Oncology, 2023)
Epithelioid inflammatory myofibroblastic sarcoma (EIMS) is a rare variant of the inflammatory myofibroblastic tumor, characterized by more aggressive clinical course and nuclear membrane staining of anaplastic lymphoma kinase (ALK) with ALK rearrangement. An elderly male came to the clinic because of an accidental abdominal mass. Abdominal and pelvic enhanced CT revealed a tumor apparently orginated from mesenchymal tissue. Subsequently, the abdominal mass and multiple organ resection was performed, and the mass was pathologically confirmed as EIMS. The patient developed Clavien-Dindo Grade III postoperative complications and was discharged after his condition improved. He received doxorubicin monotherapy after operation, but only one cycle was administered due to severe vomiting. The follow-up of 5 months after operation showed no evidence of recurrence. Given the rarity of EIMS, and ALk inhibitors have a long and robust effect on patients with ALK gene tumors, it is very important for clinicians to be familiar with the clinicopathological features of EIMS, which will contribute to the accurate diagnosis of EIMS and reduce misdiagnosis.